Emulgel: A Cutting Edge Approach for Topical Drug Delivery System - Jain, Anjali; Kumar, Prashant; Verma, Anurag; Mohanta, Bibhash Chandra; Ashique, Sumel; Pal, Radheshyam; Kumar, Shubneesh; Mishra, Neeraj (Current Drug Research Reviews, 2025)
Emulgel is considered an advanced leading form of topical drug delivery system. It possesses the quality of a dual control drug mechanism for drug release as it holds the properties of both gel as well as emulsion. Emulgel is capable of overcoming the problems of the conventional route of topical drug delivery, like low spreadability and stickiness with the delivery of hydrophobic drugs, enhanced bioavailability at the local site of action, no greasy texture, and ensuring patient compliance. An emulsion is used either w/o or o/w, and the drug can be incorporated into the suitable phase of the emulsion. After that, the emulsion is incorporated into the gel phase. Several factors like oil phase, gelling agent, and emulsifier can affect the efficacy and stability. This advancement is beneficial not only for dermatology but also for cosmetology as well. Currently, emulgel-based formulations are used for the delivery of anti-inflammatory, analgesic, anti-acne, and antifungal drugs with a wide array of exploration.
Keywords: drug delivery system